Traditional conservation and human-primate conflict in Ujungjaya Village Community, Ujung Kulon, Banten, Indonesia - SIDIK PERMANA; Ruhyat Partasasmita; JOHAN ISKANDAR; ENENG NUNUZ ROHMATULLAYALY; BUDIAWATI S. ISKANDAR; NICHOLAS MALONE (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Permana S, Partasasmita R, Iskandar J, Rohmatullayaly EN, Iskandar BS, Malone N. 2020. Traditional conservation and human-primate conflict in Ujungjaya Village Community, Ujung Kulon, Banten, Indonesia. Biodiversitas 21: 521-529. In the past, rural Sundanese people’s interactions with wild animals, including nonhuman primates (hereafter ‘primates’), is influenced by traditional ecological knowledge (TEK) with foundations in various myths and beliefs. Today, because of environmental changes, development of a market economy, cultural change, and the enhancement of agricultural technology, the beliefs and practices associated with TEK have eroded. We aim to describe the present perceptions of primates by the Sundanese people of Ujungjaya Village, Sumur Subdistrict, Ujung Kulon, Banten Province, and demonstrate how these myths and beliefs manifest in behavior towards primates. We use qualitative methods based on an ethnobiological approach to gain insight into people’s perceptions of their natural surroundings. Our results show that the people of Ujungjaya still maintain deep perceptions that are manifested in stories, songs, poems, spells, and invocations that prohibit the killing of primates. However, on their own, these manifestations are insufficient to protect primates from harm as the penetration of market economies and the fragmentation of habitats create the conditions for increased human-primate conflict. Indeed, the people of Ujungjaya sometimes hunt and capture primates for consumption, trading, and medicinal use. As such, laws and regulations designed to promote conservation are insufficient without an understanding of the cultural and socio-economic aspects of people’s lives.